System of information security in business organizations with a proposed model to meet the threats of the system - amal abid mohammad ali (Iraqi Journal for Administrative Sciences, 2024)
Contribute to information technologies in the policy-making performance in the organization, and reflect the hallmark of today's world, and is the index of the survival and success of organizations, so it became information security topics vital to the fact that any information system is exposed to many potential threats and this requires the creation of effective system to protect the information. The research subject of information security in business organizations and potential threats facing it with the presentation of a proposed model included the steps to create the system and procedures to meet the threats of the system, and conclude Find a set of recommendations, which may be considered Kmttlebatt necessary to apply the mechanism of protection of information in our organizations of Iraq in order to ensure the confidentiality of information, and integration of , availability, and integrity of their content, and determine the responsibility of the holder.